#AllCatsAreBeautiful: Ambient affiliation and the visual-verbal representation and appreciation of cats in online subversive discourses. (January 2022) - Fryer, Daniel Lees
This paper investigates the topics and affiliations associated with the hashtag #AllCatsAreBeautiful on the social media platform Twitter. Drawing on concepts from social semiotics (systemic functional theory) and critical animal studies, the paper identifies a number of potentially overlapping topics or fields, including anti-policing, the commodification of nonhuman animals, gender and sexism, and body image or body-shaming, as well as a more general positive appreciation or admiration of cats. The paper discusses how people position themselves in relation to those topics, through patterns of ideational and attitudinal meanings, and how cats are represented and appreciated visually, verbally and intersemiotically. Cats, in this context, play an important role in struggles for social justice, symbolizing freedom and resistance as well as love and solidarity. #AllCatsAreBeautiful highlights topics or spaces around which bonds can be made and communities of shared values or interests can be co-constructed.